Chronic stress influences the immune system through the thyroid axis - Cremaschi, Graciela Alicia (2000)
The aim of the present work was to analyze the effect of chronic stress on thyroid axis and its influence on the immune response. For this purpose a murine model of chronic stress was developed to evaluate and to correlate thyroid hormone levels with humoral alloimmune response. Results show a reduction in serum levels of thyroid hormones, specially a significant decrease in serum levels of tri-iodotyronine (T3) in stressed animals. On the other hand, alloimmunization was not able to induce an early increment in T3 and thyroxine (T4) levels as it was previously reported in normal animals. In addition, lower titers of alloantibodies were obtained in animals under stress conditions as compared to normal mice. The sustitutive T4 treatment in stressed animals increased significantly alloantibody production as well as the early increment in thyroid hormones after antigenic challenge. These findings suggest that chronic stress induces an alteration of the function of thyroid axis that alters the immune response. (C) 2000 Elsevier Science Inc.